Association between acute kidney injury and prognoses of cardiac surgery patients: Analysis of the MIMIC-III database - Sun, Chun; Chen, Deqing; Jin, Xin; Xu, Guangtao; Tang, Chenye; Guo, Xiao; Tang, Zhiling; Bao, Yixin; Wang, Fei; Shen, Ruilin (Frontiers in Surgery, 2023)
Background: Acute kidney injury (AKI) is the most common major complication of cardiac surgery field. The purpose of this study is to investigate the association between acute kidney injury and the prognoses of cardiac surgery patients in the Medical Information Mart for Intensive Care III (MIMIC-III) database. Methods: Clinical data were extracted from the MIMIC-III database. Adult (≥18 years) cardiac surgery patients in the database were enrolled. Multivariable logistic regression analyses were employed to assess the associations between acute kidney injury (AKI) comorbidity and 30-day mortality, 90-day mortality and hospital mortality. Different adjusting models were used to adjust for potential confounders. Results: A total of 6,002 patients were involved, among which 485 patients (8.08%) had comorbid AKI. Patients with AKI were at higher risks of prolonged ICU stay, hospital mortality, 90-day mortality (all P<0.001), and 30-day mortality (P=0.008). AKI was a risk factor for hospital mortality (Models 1 and 2: both P<0.001), 30-day mortality (Model 1: P=0.034; Model 2: P=0.016) and 90-day mortality (Models 1 and 2: both P<0.001). Conclusions: Comorbid AKI increased the risk of hospital mortality, 30-day mortality, and 90-day mortality of cardiac surgery patients in the MIMIC-III database.